The Judge's Authority in Issuing Rehabilitation Decisions for Narcotics Abuse is Reviewed Based on Law No.35 of 2009 - Eka Kurniawatie (Civiliza Publishing, 2026)
The authority of judges to impose rehabilitation decisions for narcotics abusers constitutes a crucial component of a justice system oriented toward protection and recovery. Under Law Number 35 of 2009 on Narcotics, particularly Articles 54, 103, and 127, judges are empowered to order medical and/or social rehabilitation for addicts and victims of abuse. This framework reflects a shift from a purely punitive approach to one that emphasizes therapeutic and restorative justice. This study analyzes the legal basis of such authority and finds that judicial discretion is applied within clear normative limits. Decisions must be supported by integrated assessment results, evidence that the defendant is an abuser or addict, and confirmation of non-involvement in illicit trafficking networks. In practice, judges consider juridical, sociological, and psychological factors when determining whether rehabilitation or imprisonment is appropriate. The findings highlight that rehabilitation decisions play a strategic role in achieving the broader objectives of criminal law, including recovery, prevention, and reduction of recidivism. Judges act as key actors in balancing legal certainty, utility, and justice. Effective implementation requires consistent application of legal norms, strong inter-agency coordination, and robust assessment mechanisms. Ultimately, rehabilitation serves not only as a legal instrument but also as a means of protecting human rights and facilitating the social reintegration of offenders.